The Differentiation between Premenstrual Tension Syndrome and Dysmenorrhea in Young Age Group in Kerballa City: Cross-Sectional Study - Manal Nasih Ahmed Hamdan1 Maysaloon Adnan Abdul Razzak2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The repeated psychological and physical symptoms that occur during the luteal phase of menstrual cycle and relief with menstruation called Premenstrual syndrome.The aim of study is to identify the symptoms of dysmenorrhea and premenstrual tension syndrome in young age group female and how can differentiate between these two symptoms.Material & Method: The study was across sectional which was conducted with 259 students randomly selected from Karbala secondary nursery school of girls ,Their ages ranged from (range 15-29 years) with mean age 17.85±1.920 years. A questionnaire was used to collect the data, and was distributed randomly to all students in 3 classes in period from October 2017 to May 2018.Results :259 girl shared in this study with mean age 17.85±1.920 years (range between 15-29 years) . 96.2%.Out of 259 , 205 had PMS (79.15%) with different symptoms.Most patients with PMS , developed dysmenorrhea (77. 5%) , There was significant difference between them p value (<0.001).Conclusion: high rate of young girl had premenstrual syndrome .The diagnosis of PMS is generally undervalued due to different features for PMS are used in different research. Though dysmenorrhea would distort the physicians about the actual giving symptoms from these women .